Accounting Information System and SMEs’ Financial Performance in Indonesia - Thalia Medina Lopung; Ronald Rulindo (Universitas Kristen Maranatha, 2023)
This study aims to investigate the effect of accounting information system (AIS) characteristics, namely broad scope, timeliness, aggregation and integration to financial performance of Small and Medium Enterprises (SMEs) in Indonesia. This study employs quantitative method and collects data from SMEs who do bookkeeping either manually or use more advance technologies. Multiple regression was applied in the analysis. The study's findings indicate that AIS has positive impact on SMEs’ financial performance, particularly due to the broad scope and timeliness aspects. This study, therefore, recommends SMEs to adopt AIS that employs those aspects in order to assist them to generate better performance. Keywords: Accounting Information System, Broad Of Scope, Timeliness, Aggregation, Integration, and Financial Performance